2020
DOI: 10.1021/acs.analchem.0c03330
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Liquid Chromatography and Tandem Mass Spectrometry to Electrophoresis for In-Depth Analysis of Glycosaminoglycan Drugs: Heparin and the Multicomponent Sulodexide

Abstract: Glycosaminoglycans (GAGs) contribute to the treatment of many human diseases, especially in the field of thrombosis, because of their anticoagulant activity. GAGs interrupt the coagulation process by interacting with multiple coagulation factors through defined sequences within their linear and negatively charged chains, which are not fully elucidated. Numerous methods have been developed to characterize the structure of pharmaceutical GAGs, including intravenously or subcutaneously administered heparin and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…S1), followed by the introduction of PmHS2 under the control of an inducible promoter. Disaccharide analysis based on the degradation of polysaccharides by heparosan endo-β-eliminase HepIII ( 26 ) demonstrated that KfiA Δ strains lost K5 capsule-synthesis activity, but expression of PmHS2 could rescue this disability (fig. S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1), followed by the introduction of PmHS2 under the control of an inducible promoter. Disaccharide analysis based on the degradation of polysaccharides by heparosan endo-β-eliminase HepIII ( 26 ) demonstrated that KfiA Δ strains lost K5 capsule-synthesis activity, but expression of PmHS2 could rescue this disability (fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…To verify that azido and alkyne incorporation was limited to K5 capsular polysaccharide, we subjected the GlcNAz- and GlcNAl-supplemented K5ASSH cells to digestion with heparosan endo-β-eliminase HepIII ( 26 ), which specifically targets the α-1,4 glycosidic bonds between GlcNAc (or its analogs) and GlcA residues. We observed an overall downshift, almost disappearance, of the azide-dependent or alkyne-dependent fluorescence, consistent with degradation of the heparosan (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass spectrometry plays a key role in the structural characterization of glycans, proteins, glycan–protein interactions, and protein–protein interactions ( Britt et al, 2022 ; Grabarics et al, 2022 ; Sheng et al, 2021 ; Zhang and Chi, 2021 ). Shotgun proteomics based on liquid chromatography−tandem mass spectrometry (LC−MS/MS) and database search are widely used for the qualitative and quantitative analysis of proteins in complex biological samples ( Huang and Wang, 2021 ; Marques et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%